A detailed characterization of congenital defects and mortality following moderate X‐ray doses during neurulation. Issue 6 (28th November 2017) - Craenen, Kai; Verslegers, Mieke; Buset, Jasmine; Baatout, Sarah; Moons, Lieve; Benotmane, Mohammed Abderrafi
Abstract : Background: Both epidemiological and animal studies have previously indicated a link between in utero radiation exposure and birth defects such as microphthalmos, anophthalmos, and exencephaly. However, detailed knowledge on embryonic radiosensitivity during different stages of neurulation is limited, especially in terms of neural tube defect and eye defect development. Methods: To assess the most radiosensitive stage during neurulation, pregnant C57BL6/J mice were X‐irradiated (0.5 Gy or 1.0 Gy) at embryonic days (E)7, E7.5, E8, E8.5, or E9. Next, the fetuses were scored macroscopically for various defects and prenatal resorptions/deaths were counted. In addition, cranial skeletal development was ascertained using the alcian‐alizarin method. Furthermore, postnatal/young adult survival was followed until 5 weeks (W5) of age, after X‐irradiation at E7.5 (0.1 Gy, 0.5 Gy, or 1.0 Gy). In addition, body and brain weights were registered at adult age (W10) following X‐ray exposure at E7.5 (0.1 Gy, 0.5 Gy). Results: Several malformations, including microphthalmos and exencephaly, were most evident after irradiation at E7.5, with significance starting respectively at 0.5 Gy and 1.0 Gy. Prenatal mortality and weight were significantly affected in all irradiated groups. Long‐term follow‐up of E7.5 irradiated animals revealed a reduction in survival at 5 weeks of age after high dose exposure (1.0 Gy), while lower doses (0.5 Gy, 0.1 Gy) did not affect brain and body weight at postnatal week 10. Conclusions: With this study, we gained more insight in radiosensitivity throughout neurulation, and offered a better defined model to further study radiation‐induced malformations and the underlying mechanisms.